(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
Syrian natural zeolit was used to study the adsorption of phenol from aqueous solutions. Batch method was used to study the adsorption process. The results showed that the adsorption process accurs rabidly at the first time and the equilibrium achieved after 120min . The adsorption process performed in the rang of PH (3-10). The adsorption of phenol increased by increasing of PH value up to(6-7) and then decreased. The temperature affect the adsorption process and the results showed that the increasing of the temperature leads to decreasing of the adsorption of phenol.The maximum adsorption amount of phenol was 8 mg/g at 25C0 when the initial concentration of phenol was 60mg/l. Adsorption amount of phenol increased when the adsorbent dosage increased up to 0.3g of zeolite. The resulted data of the adsorption isotherm were fitted with Langmuire model and the monomolecular layer adsorption formed on the surdace of the adsorbent.